Adaptation of Mother’s Character in Putu Wijaya’s Monolog “Ibu Sejati” - Andi Aryani (Institut Seni Indonesia Surakarta, 2022)
The Bugis-Makassar cultural community has a firm and courageous character. The character can be created through the cultural values contained in the Panngaderreng concept (ade, rapang, wari, bicara, sara). The Monolog, Ibu Sejati by Putu Wijaya, tells of a woman who is in a dilemma, having to choose between her son making a crime or enforcing the law. This study aims to create the character of the mother in Putu Wijaya’s Monolog, IbuSejati, based on the Panngaderreng concept. The reseach on the creation of this Monolog is a form of adaptation, namely examining the female characters of Bugis-Makassar and embodied in performances.